1993
DOI: 10.3109/00016489309135782
|View full text |Cite
|
Sign up to set email alerts
|

Ultracytochemical Study of Ouabain-sensitive K+-dependent p-nitro-phenylphosphatase Activity in Stria Vascularis of Reserpinized Guinea Pigs

Abstract: In order to clarify the effect of reserpine on the Na(+)-K+ active transport in the stria vascularis we investigated the localization of ouabain-sensitive K(+)-dependent p-nitro-phenylphosphatase (K-NPPase) activity in the stria vascularis of reserpinized guinea pigs using the cerium-based method. The K-NPPase activity in marginal cells differed from cell to cell, and was almost completely absent in some cells. These results are consistent with the previous results and suggest that Na(+)-K+ active transport in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…The electron dense precipitates representing pump sites over DCs, kidney and choroid plexus cells were always located on the secretory cells. A faithful reproduction of our previous ultrastructural observations of histochemically labeled avian dark cells (Yoshihara et al , 1990 and reproduction obtained by others with a similar method (Akisaka and Gay 1986;Kanoh et al 1993) was obtained. Na + /K + -ATPase in fluid-controlling epithelia Since the first demonstration of the unique ionic composition of the endolymph, several mechanisms for ion regulation and cochlear fluid homeostasis have been proposed.…”
Section: Fluorescent Indication Of Idc Functionsupporting
confidence: 74%
See 1 more Smart Citation
“…The electron dense precipitates representing pump sites over DCs, kidney and choroid plexus cells were always located on the secretory cells. A faithful reproduction of our previous ultrastructural observations of histochemically labeled avian dark cells (Yoshihara et al , 1990 and reproduction obtained by others with a similar method (Akisaka and Gay 1986;Kanoh et al 1993) was obtained. Na + /K + -ATPase in fluid-controlling epithelia Since the first demonstration of the unique ionic composition of the endolymph, several mechanisms for ion regulation and cochlear fluid homeostasis have been proposed.…”
Section: Fluorescent Indication Of Idc Functionsupporting
confidence: 74%
“…Pump sites decoration in the plasma membrane of kidney and choroid plexus were included as a control for the method specificity. DC pump sites were labeled as described in the original work (Mayahara et al 1980), corroborated by us (Yoshihara 1984;Yoshihara andIgarashi 1986, 1987;Yoshihara et al ,1990 and others (Akisaka and Gay 1986;Kanoh et al 1993). The results suggest that the techniques utilized to test iDCs viability are useful for future in vitro tests of DCs function.…”
Section: Methodssupporting
confidence: 52%
“…In the cochlea, K-NPPase activity in the stria vascularis was shown to be almost completely decreased after reserpine administration (Kanoh et al 1993a. In a paper to be published in the near future, K-NPPase activity in the kidney was reported to be similarly suppressed after reserpine administration.…”
Section: Discussionmentioning
confidence: 85%
“…The abundance of the ␣ 2 subunit isoform was reduced by 41% in vas deferens homogenates obtained from animals treated with reserpine compared with untreated controls. Using a ceriumbased method (Kobayashi et al 1987), Kanoh et al (1993a) and Kanoh (1994) investigated the localization of K-NPPase activity in the stria vascularis of reserpinized guinea pigs and found that K-NPPase activity was decreased from Day 3 to Day 20 after reserpinization. K-NPPase is the second component of the Na,K-ATPase complex, which represents the dephosphorylation step in the sodium pump cycle (Judah et al 1962).…”
mentioning
confidence: 99%
“…Using a cerium-based method (11), Kanoh (12,13) reported that reserpine decreased ouabain-sensitive, K + -dependent p-nitrophenylphosphatase (K-NPPase) (14) activity in strial marginal cells from day 3 to day 20 after treatment. Kanoh also investigated (15) the cytochemical localization of K-NPPase activity in the facial nerve of reserpinized guinea pigs, and reported that the reaction product of the enzyme activity could be detected on the axolemma of the Ranvier nodes, but was undetectable on the other parts of the axolemma.…”
Section: Introductionmentioning
confidence: 99%